Impact of COVID-19 on livestock sector in India: An economic analysis - Swain, Braja; Kennady, Vijayalakshmy; Rahman, Habibar (2020)
Coronavirus or COVID-19 has made a devasting loss to the different sectors of the world. Out of which, livestock sector is the one among them which is not directly affected by the virus, but indirectly has created a great economic loss to the sector mainly because of the lockdown. The lockdown has created several issues i.e. decline in the demand as well supply of animal products. In addition, there is a rumour that COVID-19 can be spread through the consumption of animal products. The coronavirus pandemic has been a public health emergency all over the world, and the continuous phase of lockdown for a long period has created a major impact in the different sector of the world. Likewise in India, various sectors have been drastically affected and livestock and poultry sector which is the fastest growing sector in India is tremendously affected. There is a great impact of COVID-19 and its associated lockdown on livestock and poultry sectors in India that includes impact on dairy and associated value chain, poultry, nutrition and health care and labor availability. In this context, the present article is going to depict the economic analysis that indirectly reflects the impact of COVID-19 outbreak in India on the livestock sector.